(untitled) (Вісник: Міжнародні відносини, 2025)
Background. Ethnic conflicts provoked by unsolved complex issues in international and interfaith relations both between and within states have been an integral part of contemporary history of international relations. West Europe is no exception in this particular case, because, besides ethnic tensions caused by migration crisis, it bestows a series of issues concerning disputed status of native ethnic minorities. The South Tirol case shows how these issues can be solved. Methods. The research combines political realism and historical method which is based on chronologically studying the emerging, shaping and developing national and ethnic issue in South Tirol. Results. The evolution of the South Tirol case and ways of its resolving in contemporary history (politically and legally) has been examined. Conclusion. The ethnic issues of South Tirol can be effectively solved when Austria and Italy apply relevant democratic mechanisms which take both national interests and national minority rights residing on their respective territories into account.